Epithelial antibiotic induced in states of disease - Stolzenberg, Ethan D. (The National Academy of Sciences of the USA, 1997)
Epithelial defensins provide an active defense against the external microbial environment. We investigated the distribution and expression of this class of antimicrobial peptides in normal cattle and in animals in varying states of disease. β-defensin mRNA was found to be widely expressed in numerous exposed epithelia but was found at higher levels in tissues that are constantly exposed to and colonized by microorganisms. We observed induction in ileal mucosa during chronic infection with Mycobacterium paratuberculosis and in bronchial epithelium after acute infection with Pasteurella haemolytica. It has been proposed that expression of antimicrobial peptides is an integral component of the inflammatory response. The results reported here support this hypothesis and suggest that epithelial defensins provide a rapidly mobilized local defense against infectious organisms.